THE RIGHT TO CARE AND THE THIRD SECTOR: WE POINT OUT FROM LAW NO. 15.069, OF DECEMBER 23, 2024 - Eduardo Sabo Paes, José; Edstron S. Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2025)
Through the bibliographic review technique and the hypothetical-deductive method, the right to care was demonstrated and the relevance of the Third Sector’s actions in light of Law No. 15.069, of December 23, 2024. The entire historical path of human dignity was inventoried and the need for the right to care to have a broad legal basis and to be able to be a factor of social transformation was pointed out, especially for people who survive on the extreme poverty line in Brazil.